Artivism in 21st-Century Russia and the Rhetoric of the Absurd - Dunaeva, Cristina Antonioevna (Farol, 2025)
This article addresses the use of absurdism and irony in the artworks of the historical avant-gardes of Eastern Europe, in their relation to conceptual art developed informally in the Soviet Union and contemporary artivism. The poetics of the absurd appear as important characteristics of contemporary art, in its artivist and actionist aspects, prominent in the Russian art scene in the 21st century. The importance of the artistic work of Dmitri Prigov, a representative of Soviet informal art and Moscow conceptualism, is highlighted; as is Prigov’s influence on artistic collectives such as Voina and Pussy Riot, examples of contemporary artivism. Finally, some aspects of the work of artivists such as Katrin Nenacheva and Artyom Loskutov are discussed.